2021
DOI: 10.1038/s41598-020-77775-8
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic patterns of YAP1 expression and cellular localization in the developing and injured utricle

Abstract: The Hippo signaling pathway is a key regulator of tissue development and regeneration. Activation of the Hippo pathway leads to nuclear translocation of the YAP1 transcriptional coactivator, resulting in changes in gene expression and cell cycle entry. Recent studies have demonstrated the nuclear translocation of YAP1 during the development of the sensory organs of the inner ear, but the possible role of YAP1 in sensory regeneration of the inner ear is unclear. The present study characterized the cellular loca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Unfortunately, there are few studies on the role of the Hippo/YAP signaling pathway in auditory organs. Recently, YAP has been reported to be required for HC proliferation and differentiation in the inner ear [67][68][69]. However, whether the Hippo/ YAP signaling pathway is required for HC survival has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are few studies on the role of the Hippo/YAP signaling pathway in auditory organs. Recently, YAP has been reported to be required for HC proliferation and differentiation in the inner ear [67][68][69]. However, whether the Hippo/ YAP signaling pathway is required for HC survival has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…inhibitors and others [29][30][31][32] (Figure 3). Small molecule inhibitors of the enzyme γ-secretase, originally developed for Alzheimer's disease, have been repurposed as potential hearing loss therapeutics due to their ability to modulate Notch signaling, a critical pathway in HC development and non-mammalian regeneration.…”
Section: Hair Cell Regenerationmentioning
confidence: 99%
“…Currently, most research into mammalian HC regeneration places a heavy emphasis on several key signaling pathways upstream of Atoh1 that have been shown to be critical for HC development and regeneration in fish and birds. Some of these pathways and genes include Wnt / β‐catenin , Notch, P27 kip1 , Gfi, MYC, Hippo/YAP , and most recently, epigenetic regulation by histone deacetylase (HDAC) inhibitors and others 29 , 30 , 31 , 32 (Figure 3 ). Small molecule inhibitors of the enzyme γ‐secretase, originally developed for Alzheimer's disease, have been repurposed as potential hearing loss therapeutics due to their ability to modulate Notch signaling, a critical pathway in HC development and non‐mammalian regeneration.…”
Section: Hearing Loss Mechanisms and Therapeutic Strategiesmentioning
confidence: 99%
“…The findings by Rudolf et al suggested that cellular damage overcomes inhibitory Hippo signaling and facilitates regenerative proliferation in non-mammalian utricles, whereas suppressing YAP-TEAD signaling in mammalian utricles contributes to maintaining the proliferative quiescence 26 . The different cellular localizations of YAP may partially account for the regenerative abilities of the utricles in chicks 27 . However, most studies on the Hippo signaling pathway have focused on its function in inhibiting cell proliferation and promoting withdrawal from the cell cycle in the inner ear, and not on its application for promoting HC regeneration.…”
Section: Introductionmentioning
confidence: 99%